The diatom genus Oricymba in Vietnam and Laos with description of one new species, and a consideration of its systematic placement - Kulikovskiy, Maxim Sergeevich; Glushchenko, Anton; Kociolek, John Patrick (Phytotaxa, 2015)
Species from the genus Oricymba are studied from freshwater ecosystems of Vietnam and Laos. Three species were found in Vietnam, namely O. japonica, O. subovalis and O. perjaponica comb. nov. The two last species are new taxa for the diatom flora of Vietnam. A new species is described from Laos, O. voronkinae sp. nov., and its morphology is documented with light and scanning electron microscopy. Oricymba voronkinae sp. nov. represents the first documented occurrence of the genus Oricymba in Laos. Our findings provide new information about the morphology and species distribution of the genus Oricymba in Indochina. We discuss the systematic position of Oricymba within the Cymbellales.